Penguatan Literasi Kesehatan Mental Melalui Modul Bilingual dan Learning Management System Bersama Komunitas Halo Jiwa Indonesia - Zuhdy Idham, Afif; Rauf, Wahyuddin; Taufik, Taufik; Muhiddin, Syurawasti; imran, Ahmad Fadhil; Sumarwadji, Hafid; Idham, Azmul Fuady (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This community service program was conducted in response to the need of Halo Jiwa Indonesia Community to improve the quality of standardized, accessible, and digitally supported mental health education. The main objective of the program was to strengthen volunteers’ capacity in understanding mental health literacy, using bilingual learning materials, utilizing a digital learning system, and developing educational content for public dissemination. The activity was implemented on August 17, 2026, in Makassar, involving the management team and volunteers of Halo Jiwa Indonesia Community. The implementation method consisted of needs analysis, development of bilingual learning modules, volunteer training, introduction to a digital learning platform, mentoring in educational content production, and activity evaluation. The participants were divided into two groups, namely community managers who contributed to program alignment and volunteers who served as the main participants in the training activities. The results showed the development of a bilingual mental health education module, increased volunteer understanding of empathic communication and psychological first aid, the preparation of digital educational content, and improved readiness of the partner community to manage volunteer learning more systematically. The program provided benefits in strengthening community capacity, standardizing educational materials, and expanding public access to inclusive mental health information. This program concludes that collaboration between higher education institutions and community organizations through bilingual modules and digital learning systems is an important strategy for community empowerment. Further programs are recommended to measure broader impacts on community beneficiaries.